The relationship of tennis-specific motor abilities and the competition efficiency of young female tennis players - Filipcic, A.; Filipcic, T. (Kinesiology, 2005)
A sample of 96 young female tennis players, aged 13 and 14 years, was included in the research aimed at establishing the influence of selected tennis-specific motor abilities on the competition efficiency of young tennis players. The selected tennis-specific motor variables were: muscular power of the arms and shoulders (MBP), muscular power of the legs (QJ), muscular strength of the trunk (SU60), acceleration (R20), shuttle run ability (R9x6), speed of alternate arm movements (TAP20), flexibility of the back (FBB), flex-ibility in the shoulders (TS), flexibility of hips (FH), agility (FAN), coordination (OC), hand-eye coordination (RTBR) and dynamic balance (TLB). In defining the criterion variable (competition efficiency), all the tournaments for female tennis players which had taken place in the period of the last competition season were taken into account. The results revealed a statistically significant connection between the group of selected tennis-specific motor variables and the criterion variable - competition efficiency (0.83). The regression analysis results show that the system of predictor variables explains 69% of the variance of the criterion variable. Among the selected variables there is a statistically significant connection between seven of them and the variance of the criterion variable. These variables measure the muscular power of arms and shoulders (MBP), acceleration (R20), flexibility in the shoulders (TS), flexibility of the back (FBB), flexibility of hips (FH), hand-eye coordination (RTBR) and dynamic balance (TLB).